2022
DOI: 10.7759/cureus.32279
|View full text |Cite
|
Sign up to set email alerts
|

Morphometry of Conus Medullaris in the Saudi Population and Its Clinical Importance

Abstract: The objective of this article is to evaluate the morphometry and termination of conus medullaris (CM) in the eastern province of Saudi Arabia. MethodologyThe lumbar spine magnetic resonance imaging (MRI) scans of 179 citizens of Saudi Arabia were selected and divided into males and females. Parameters such as the level of termination of CM, the length/width of CM, and its termination were reported. ResultsThe maximum number of males and females were observed in the less than 20 years age group as 23 (25.5%) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Previous studies at similar sites in other countries found the prevalence to be 15% which gives us estimate of sample size to be about 196, while previous studies conducted in Nigeria, Korea, and Saudi Arabia used sample size 187, 177 and 179 respectively. 5,7,8 Therefore, we confined our sample size at 202. MRI scans were reviewed by the consultant radiologists having more than five years of experience on MR spine reporting.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies at similar sites in other countries found the prevalence to be 15% which gives us estimate of sample size to be about 196, while previous studies conducted in Nigeria, Korea, and Saudi Arabia used sample size 187, 177 and 179 respectively. 5,7,8 Therefore, we confined our sample size at 202. MRI scans were reviewed by the consultant radiologists having more than five years of experience on MR spine reporting.…”
Section: Methodsmentioning
confidence: 99%